Effects of different types of Syzygium Polyanthum leaves extracts on blood pressure of anaesthetized Spontaneously Hypertensive rats - Ismail, Azlini; Wan Ahmad, Wan Amir Nizam (2017)
Background: Syzygium polyanthum leaves are used traditionally for treatment of hypertension. Our previous study showed that S. polyanthum leaves decoction caused significant reduction in blood pressure of Spontaneously Hypertensive rats (SHR) but the bioactive compound(s) is yet unknown. Objective: The study aimed to identify the most promising S. polyanthum leaves extract to be subsequently fractionated for the purpose of isolating the bioactive compound(s) responsible for the reduction in blood pressure of SHR. Materials & Methods: SHR rats were anaesthetized using sodium pentobarbital at 60 mg/kg, administered intra-peritonelly. Aqueous (ASP), methanol (MSP), ethyl acetate (EASP) and n-hexane (HSP) extracts of S. polyanthum leaves at increasing doses of 1, 10, 40, and 70 mg/kg were intravenously administered via left jugular vein of SHR (n=6, each group). The changes in hemodynamic parameters including beat-to-beat mean arterial (MAP), systolic (SBP) and diastolic (DBP) blood pressures were recorded through cannulated right main carotid artery using BIOPAC® Recording System. Results: Only EASP, MSP and ASP at doses 40 and 70 mg/kg significantly reduced MAP, SBP and DBP of SHR (P<0.001). Notably, ASP produced the highest reduction in MAP, SBP, and DBP of SHR compared to the other two extracts. However, at the dose of 70 mg/kg, ASP caused sudden drop in blood pressure, and subsequently caused mortality in the tested SHR. Conclusion: It is postulated that the bioactive compound(s) that is(are) responsible for the reduction in blood pressure of SHR by S. polyanthum leaves is(are) polar or semi-polar compound(s). ASP should be fractionated and tested in future experiments.